Content Analysis of Ocean Literacy as the Basis of Blue Curriculum’s Framework in Vocational Education - Hardika, Mutia; Widiaty, Isma; Jubaedah, Yoyoh (Universitas Ahmad Dahlan, 2024)
This research aims to analyse the need for Ocean Literacy content indicators to be adapted as the basis of Blue Curriculum's framework in Vocational Education. The Systematic Literature Review (SLR) method was used as the research approach using carefully selected articles from the Sciencedirect database. The selected articles were those published between 2018 and 2023. The PRISMA method was used to filter out documents that did not fit the inclusion and exclusion criteria outlined in this study. After examining and reviewing the selected articles, it was found that there are several indicators that can be put forward in Ocean Literacy content. These are ocean potentials, ocean strategy and management, ocean activities and their impacts on marine ecosystems, ocean-related tourism and culture, ocean sustainable development, and ocean-related policies. This discovery is expected to be integrated into the educational curriculum in vocational education as one of the strategies in managing various marine potentials for sustainable development.